(untitled) (Research, Society and Development, 2022)
Objective: to identify the effects of exercises with continuous or intermittent restriction of blood flow on strength, endurance and functional capacity. Methodology of an integrative literature review, where there was the inclusion of articles that integrate the relationship with a thematic proposal from 2019 to 2022, available in English and Portuguese; in addition to theses, dissertations and monographs. Exclusion articles were literature review articles, articles or abstracts published in conference proceedings; as well as letters from editors and preprints. Results: There were 223 articles, in which all had their titles and abstracts read, after that, 200 articles were excluded for not meeting the readability criteria, leaving 23 articles that were read carefully in the integrability; full reading, 7 articles were selected for tabulation, presented and demonstrated their level of proof, after which they met the strategy. Final considerations: In view of the scientific findings, it was observed that it can be considered an important tool in the gain of muscle hypertrophy, resistance and improvement of functional aspects in the most varied audiences. In addition, the RFS the application of exercises with low loads that there is joint compromise, promoting similar results when compared to optimized adjustments.